Pengaruh variasi komposisi MnFe2O4 terhadap sifat magnetik nanokomposit MnFe2O4/PANi yang disintesis dengan metoda sol – gel spin coating (MnFe2O4 composition influence on the magnetic properties of MnFe2O4 / PANi nanocomposites synthesized by the sol-gel spin coating method) - Zhafrandy Eka Senida; - Ramli; - Ratnawulan; - Hidayati (PILLAR OF PHYSICS, 2019)
Currently theeprogressoof material nanocomposite can be applied for some of electronic device, bio medic, and electronic engineering. This is because nanocomposite has multifunction of magnetic properties. Most of device use nanoparticles was made from ferrite material, such as MnFe2O4 with high electrical performance, high magnetic permeability. And as matrix used PANi with good thermal stability and high conductivity. With this advantages, synthesis both material can be applied for electronic device like magnetic sensor. Synthesis MnFe2O4/PANi nanocomposite material with 30%, 40%, 50%, 60%, and 70% composition variation of MnFe2O4 with Sol-Gel method has been success. MnFe2O4/PANi nanocomposite was prepared by make of Fe2O3 precursor, make MnFe2O4 and PANi solution with sol-gel method, make MnFe2O4/PANi nanocomposite with spin coating, heating, and sintering the nanocomposite. This nanocomposite characterized with XRD, FTIR, and VSM. Magnetic properties nanocomposite were measured withaa Vibrating Sample Magnetometer (VSM). Result of VSM shows value of coercivity (Hc), remanence magnetization (Mr) and saturation magnetization (Ms). Highest value offcoercivity shows in 60% composition variation with score 389,99Oe, from the value of coercivity, we can classified this nanocomposite as a hard magnet. And for the value of saturation magnetization is 1,07 memu and remanence magnetization is 0,35 memu. The applied field of nanocomposite shows in loop hysteresis with range -10000≤ H ≤10000, it show the ferromagnetic behavior. Ferromagnetic is one of material properties which needed for magnetic sensor. So can be concluded that MnFe2O4/PANi nanocomposite can be applied for magnetic sensor.